Management of mental health emergencies in elite athletes: a narrative review. Issue 12 (8th June 2019) - Currie, Alan; McDuff, David; Johnston, Allan; Hopley, Phil; Hitchcock, Mary E; Reardon, Claudia L; Hainline, Brian
Abstract : Mental health emergencies require a rapid, effective response. We searched the literature on mental health emergencies in athletes and found five papers. None of these addressed elite athletes. Nonetheless, common mental health emergencies may present in the sports environment and may place the athlete and others at risk. Sports teams and organisations should anticipate which emergencies are likely and how medical and support staff can best respond. Responses should be based on general non-sporting guidelines. We stress the importance of clinicians following standard procedures.